The feasibility of measuring calprotectin from a throat swab as a marker of infections caused by group A streptococcus: a case–control feasibility study. Issue 2 (June 2020) - Schofield, Behnaz; Gregory, Clive; Gal, Micaela; Gillespie, David; Naik, Gurudutt; Hay, Alastair; Francis, Nick
No abstract available